An easy method to determine crucial AMEI performance parameters from clinical routine data in individuals – Part 2: dynamic range. - Busch, Susan; Lenarz, Thomas; Maier, Hannes (International Journal of Audiology, 2025)
Objective: The dynamic range (DR) available to the patient is a central parameter to determine speech intelligibility in quiet. Design: In this retrospective study, the DR for the Vibrant Soundbridge implanted in individual patients was calculated using in situ thresholds of the patients and technical data of the implant system. The average DR across frequencies (0.5, 1, 2, 4 kHz) was correlated with the patients' assigned word recognition score (WRS) in quiet. Study sample: A data set of 66 cases (4 bilateral and 2 revised cases) from 60 implanted patients between 14.3–81.8 years were analysed. Results: The relationship between DR and WRS was described by a sigmoidal growth function with R2=0.6371 and a maximum WRS (upper asymptote) of 93.5%. Word recognition scores in quiet improved with increasing DR. A significant shift in performance was detected from DR bin 2 (10–20 dB, median WRS 55%) to bin 3 (20–30 dB, median WRS 80%) and from DR bin 4 (30–40 dB, median WRS 82.5%) to bin 5 (40–50 dB, median WRS 90%). Conclusion: A minimum DR of 20 dB can yield sufficient speech intelligibility in quiet in implanted patients, however, an optimum DR is suggested to be 40 dB.